Second sight - Hine, Robert V., 1921-2015 (University of California Press, 1993)
He knew he was going blind. While his sight slowly faded, he finished graduate school, became a history professor, and wrote books about the American West until, nearly fifty years old, Robert Hine lost his vision completely. When, fifteen years later, a dangerous eye operation restored partial vision and returned Hine to the world of the sighted, "the trauma seemed instructive enough" to prompt him to begin a journal. That journal is the heart of Second Sight, an engaging, sensitively written account of Hine's journey into darkness and out again. The first parts are told simply, with little anguish and no self-pity. The emotion comes when sight returns; like a child he discovers the world and its beauty anew - the intensity of colors, the sadness of faces grown older, the renewed excitement of sex and the body. With fine understanding and humorous insights that come from living on both sides of the divide, Hine ponders the relations of sighted and unsighted people. His personal search for the meaning of blindness is enriched and made universal by a discourse with other contemporary blind writers. When the author turns to humorist James Thurber, Buchenwald prisoner Jacques Lusseyran, novelist Eleanor Clark, journalist Sally Wagner, poet Jorge Luis Borges, and teacher John Hull, he clearly relishes the kinship of a brilliant, opinionated family that "apparently can't agree on much but actually agrees on a great deal." With them he shares thoughts on the acceptance and advantages of blindness, resentment of the blind, the blind as "the darlings of the handicapped," the reluctance with sex, explanations for shadow vision, and the psychological depression that often follows the recovery of sight. But Hine's professional and personal life is the heart of his narrative. His blindness was the altered state in which to learn and live, and his deliverance from blindness the spur to seek and share its lessons. What he found makes a wonderful story that embraces all of us - those who can see and those who cannot